Synchrotron X‐ray diffraction investigation of the surface condition of artefacts from King Henry VIII's warship the Mary Rose. (15th April 2020) - Dowsett, Mark G.; Sabbe, Pieter-Jan; Alves Anjos, Jorge; Schofield, Eleanor J.; Walker, David; Thomas, Pam; York, Steven; Brown, Simon; Wermeille, Didier; Adriaens, Mieke
Abstract : A new method using a high‐sensitivity X‐ray camera for a large‐range diffraction pattern is presented; it confirms the effectiveness of over 35 years of conservation treatment for brass artefacts from the Mary Rose. Abstract : Synchrotron X‐ray diffraction (XRD) measured on the XMaS beamline at the ESRF was used to characterize the alloy composition and crystalline surface corrosion of three copper alloy Tudor artefacts recovered from the undersea wreck of King Henry VIII's warship the Mary Rose . The XRD method adopted has a dynamic range ∼1:10 5 and allows reflections <0.002% of the height of major reflections in the pattern to be discerned above the background without smoothing. Laboratory XRD, scanning electron microscopy–energy dispersive spectroscopy, synchrotron X‐ray fluorescence and X‐ray excited optical luminescence–X‐ray near‐edge absorption structure were used as supporting techniques, and the combination revealed structural and compositional features of importance to both archaeology and conservation. The artefacts were brass links believed to be fragments of chainmail and were excavated from the seabed during 1981 and 1982. Their condition reflects very different treatment just after recovery, viz. complete cleaning and conservation, chemical corrosion inhibition and chloride removal only, and distilled water soaking only (to remove the chlorides). The brass composition has been determined for all three at least in the top 7 µm or so as Cu(73%)Zn(27%) from the lattice constant. Measurement of the peak widths showed significant differences in the crystallite size and microstrain between the three samples. All of the links are found to be almost chloride‐free with the main corrosion products being spertiniite, sphalerite, zincite, covellite and chalcocite. The balance of corrosion products between the links reflects the conservation treatment applied to one and points to different corrosion environments for the other two.